Disorder of digestive function in eating disorders: nutritional treatment - Djukic, Sladjana; Olajdžija, Tanja (Education and Research in Health Sciences, 2026)
Eating disorders represent complex psychiatric and metabolic conditions that, in addition to psychological and endocrinological consequences, significantly affect the function of the digestive system. Prolonged dietary restriction, episodes of binge eating, self-induced vomiting, as well as the abuse of laxatives and diuretics lead to numerous gastrointestinal disturbances, including delayed gastric emptying, bloating, abdominal pain, diarrhea, and constipation, which often persist even during remission of the disorder. These symptoms further complicate nutritional rehabilitation and may constitute a significant barrier to the recovery process. The aim of this paper is to present the mechanisms underlying digestive function disorders in individuals with eating disorders, as well as to discuss the principles and importance of appropriate nutritional treatment in the management of these disturbances. The methods include a review of relevant scientific literature available in international databases, with a focus on clinical studies, systematic reviews, and guidelines addressing gastrointestinal complications and nutritional interventions in eating disorders. The results indicate that disorders of digestive function are common, multifactorial, and largely reversible when an appropriately guided nutritional treatment is implemented. Gradual increases in energy intake, tailored food selection, adequate intake of dietary fiber and fluids, as well as the use of probiotics and prebiotics, have been shown to be key elements in the restoration of gastrointestinal function. It is concluded that understanding digestive symptoms and systematically incorporating them into the nutritional therapy plan is essential for achieving successful and sustainable recovery in individuals with eating disorders.